2019
DOI: 10.1007/s13399-019-00473-7
|View full text |Cite
|
Sign up to set email alerts
|

Production and applications of activated carbons as adsorbents from olive stones

Abstract: Olive stones have been widely used as a renewable energy biowaste source. As they are rich in elemental carbon (40-45 wt%), much research focussed on effectively converting olive stones, as precursors, into activated carbon adsorbents. However, only a few studies have concentrated on summarising the various techniques used to produce activated carbon from olive stone. This article reviews the research undertaken on the production and application of activated carbon as an adsorbent from olive stones for wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
164
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(188 citation statements)
references
References 228 publications
(241 reference statements)
1
164
1
2
Order By: Relevance
“…There is currently a reborn interest in research of the synthesis, characterization, and applications of activated carbons, as shown by recent reviews and the high number of publications on this topic that can be found in the technical literature [19][20][21][22][23][24]. Activated carbons can be synthesized from any carbonaceous precursor, such as coal [25][26][27], discarded tires [28][29][30], lignin [31][32][33], or biomass waste [34][35][36][37], among others, preferably with low inorganic content. Nowadays, most of the research is focused in the synthesis of activated carbons from biomass waste due to some unquestionable advantages: (1) this process results in the revalorization of waste, (2) the synthesized activated carbons have a lower cost since they are produced from low economic value precursors, (3) they are obtained from renewable resources, and (4) after their lifetime, the combustion of these activated carbons does not increase CO 2 accumulation in the atmosphere because this CO 2 has been previously captured during plant growth [38,39].…”
Section: Activated Carbonsmentioning
confidence: 99%
“…There is currently a reborn interest in research of the synthesis, characterization, and applications of activated carbons, as shown by recent reviews and the high number of publications on this topic that can be found in the technical literature [19][20][21][22][23][24]. Activated carbons can be synthesized from any carbonaceous precursor, such as coal [25][26][27], discarded tires [28][29][30], lignin [31][32][33], or biomass waste [34][35][36][37], among others, preferably with low inorganic content. Nowadays, most of the research is focused in the synthesis of activated carbons from biomass waste due to some unquestionable advantages: (1) this process results in the revalorization of waste, (2) the synthesized activated carbons have a lower cost since they are produced from low economic value precursors, (3) they are obtained from renewable resources, and (4) after their lifetime, the combustion of these activated carbons does not increase CO 2 accumulation in the atmosphere because this CO 2 has been previously captured during plant growth [38,39].…”
Section: Activated Carbonsmentioning
confidence: 99%
“…Adsorption on activated carbon has been widely used for the removal of a broad range of water pollutants, especially for low-to-moderate-concentration pollutants (Pérez-Candela et al 1995;Demirbas et al 2004;Khezami and Capart 2005). However, because of the high cost of activated carbon, it is desirable to search for a low-cost and efficient adsorbent for the removal of Cr(VI) (Belachew and Bekele 2019;Saleem et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is amorphous carbon based on a graphite structure, with developed porosity, high specic surface and a certain amount of oxygen-containing groups. 45,46 In contrast to the zeolite and diatomite, the activated carbon had high adsorption capacity for AOG and AB80, but scarcely adsorbed AF. This indicates the activated carbon tended to adsorb the monoazo and anthraquinone dyes with fused ring structures, where in this mode, the van der Waals forces and p-p stacking effect between the sp 2 -hybridized C atoms of the activated carbon and fused rings of the dyes molecules play a signicant role.…”
Section: Adsorption Studiesmentioning
confidence: 99%